Seasonal Photophysiological Performance of Adult Western Baltic Fucus vesiculosus (Phaeophyceae) Under Ocean Warming and Acidification - Graiff, Angelika; Bartsch, Inka; Glaser, Karin; Karsten, Ulf (Frontiers in Marine Science, 2021)
Shallow coastal marine ecosystems are exposed to intensive warming events in the last decade, threatening keystone macroalgal species such as the bladder wrack (Fucus vesiculosus, Phaeophyceae) in the Baltic Sea. Herein, we experimentally tested in four consecutive benthic mesocosm experiments, if the single and combined impact of elevated seawater temperature (Δ + 5°C) and pCO2 (1100 ppm) under natural irradiance conditions seasonally affected the photophysiological performance (i.e., oxygen production, in vivo chlorophyll a fluorescence, energy dissipation pathways and chlorophyll concentration) of Baltic Sea Fucus. Photosynthesis was highest in spring/early summer when water temperature and solar irradiance increases naturally, and was lowest in winter (December to January/February). Temperature had a stronger effect than pCO2 on photosynthetic performance of Fucus in all seasons. In contrast to the expectation that warmer winter conditions might be beneficial, elevated temperature conditions and sub-optimal low winter light conditions decreased photophysiological performance of Fucus. In summer, western Baltic Sea Fucus already lives close to its upper thermal tolerance limit and future warming of the Baltic Sea during summer may probably become deleterious for this species. However, our results indicate that over most of the year a combination of future ocean warming and increased pCO2 will have slightly positive effects for Fucus photophysiological performance.